2021
DOI: 10.1002/adfm.202111045
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible, Mechanically Strong, and Anti‐Corrosion Electromagnetic Wave Absorption Composite Film with Periodic Electroconductive Patterns

Abstract: Demand for high-efficiency electromagnetic wave (EMW) absorption composite films continues to increase with technical advances in 5G telecommunications, wearable electronics, portable devices, and deployable military applications. However, realizing flexible ultra-thin single-layer EMW absorption composite films with multifunctionality, rather than using traditional particle absorbents, is a known challenge. In this study, the authors propose a series of polyimide (PI) reinforced composite films with periodic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 67 publications
(35 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…[6][7][8] Typically, dielectric loss contains polarization and conduction loss, which are related to electron formation, transport, and aggregation. [9,10] Anion vacancy engineering has been proven to be one of the studied and effective methods to this end. As for the conduction loss, previous reports have well revealed that these anionic vacancies can shape the band structure by introducing intra-band gap states, and benefits to the improved electronic conductivity.…”
mentioning
confidence: 99%
“…[6][7][8] Typically, dielectric loss contains polarization and conduction loss, which are related to electron formation, transport, and aggregation. [9,10] Anion vacancy engineering has been proven to be one of the studied and effective methods to this end. As for the conduction loss, previous reports have well revealed that these anionic vacancies can shape the band structure by introducing intra-band gap states, and benefits to the improved electronic conductivity.…”
mentioning
confidence: 99%
“…In fact, a qualified absorber can only survive with multifunctionality in a complex environment. 5,9,10 For instance, the Ti 3 C 2 T x /carbon nano tube/ Co composite was prepared by Xiang et al 11 with a strong the minimum reflection loss (RL min ) of −85.8 dB and the flexibility, waterproof and photothermal conversion properties, which was expected to be a new generation of EMA materials. Huang et al prepared a graphene-based aerogel with excellent heat insulation and frost prevention, which provided a reference for the production of EMA materials used in complex environments.…”
Section: Introductionmentioning
confidence: 99%
“…In this case, the EMA of these samples is mainly caused by dielectric loss. The complex permittivity (ε′ and ε″), which is closely related to the dielectric loss, [55][56][57] is further investigated (Figures S23 and S24, Supporting Information). Obviously, with the increase of Cu 2+1 O phase and the decrease of amorphous carbon, the average value of complex permittivity shows a regular downward trend (ε′: 7.72.42, ε″: 6.87-0.54), [58] especially in the CuNC20 sample (Figure 4h).…”
Section: Resultsmentioning
confidence: 99%